The Effect of Cash Turnover, Account Receivable Turnover and Inventory Turnover on ROA in Mining and Quarrying Sector Companies Listed in IDX from 2017-2019 - Yulsiati, Henny; Kusnadi, Mutiara Dwi; Alif’ia, Nabilla Fitri (Westscience Press, 2025)
The purpose of this study is to assess the level of unemployment in DKI Jakarta Province by considering the Regional Minimum Wage and Population Frequency. The research method applied is quantitative, using secondary data obtained from the official website of bps.go.id. The population taken in this study covers 7 districts/cities in Bali Province, with samples taken from basic statistical data recorded at BPS DKI Jakarta, especially the Regional Minimum Wage and Population Frequency during the 2018-2022 period. This study uses the purposive sampling method to determine the sample. with a frequency of 35 observations. The hypothesis test of this study was carried out using multiple regression analysis. The test results show that the Regional Minimum Wage and Population Frequency have a positive and significant effect on the Unemployment Level. This study also concluded that Population Frequency has no effect on the Unemployment Level.